Biomechanical Evaluation of Spontaneous Repair of Osteochondral Defects in the Rabbit Knee - Fahimeh Kamali; Giti Torkaman (Shiraz University of Medical Sciences, 2014)
Background: Examination of cartilage repair in animal work is dependent upon the thickness and radius of the induced impalement. Full-thickness defects with a radius of 3 mm have been commonly used in animal studies to evaluate new procedures designed to improve the quality of articular cartilage repair. The aim of the present study was to define the biomechanical characteristics of the repair of 5×4 mm full-thickness osteochondral defects in adult male rabbits. Methods: In a controlled clinical trial study 5 mm diameter and 4 mm deep osteochondral defects were drilled in the femoral patellar groove of twenty-one rabbits, and examined at 4, 8, and 16 weeks. The left knee was kept intact and was regarded as control. The knee joints were removed, and both legs were examined biomechanically by in situ indentation method at three time intervals (4, 8, 16 weeks). The instantaneous and equilibrium elastic- modulus (after 900 second) were measured during the test. Results: There were no differences in cartilage mechanical properties (instantaneous and equilibrium elastic-modulus) in different weeks (4, 8, 16 weeks) in the two groups (P=0.08). However, significant differences were seen between the experimental and control groups in 16 weeks in instantaneous elastic_ modulus (P=0.44). It suggests that new tissue in this group had more stiffness than control in 16 weeks. Conclusion: Full-thickness osteochondral defect, measuring 5×4mm in the patellar groove of the adolescent rabbit knee healed spontaneously.